Pemilihan Vegetasi Untuk Pengendalian Longsor Lahan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
The news of flood and landslide disaster in our country was filled mass-media at all times. The occurance start from Cilacap, Purworejo, Kulonprogo, Aceh, Sumatra Barat, Jawa Timur, Menado, and at the end of 2008 happened in Cianjur and Bali. It taken a lot of victims and properties, so that come up some question why it happend and how to anticipated for reduce the negatif impact. Indonesia as tropical country have highly rainfall intensity in some region, in others have landform hove, hill and mountain with high potencial lands ide hazard. Majority the people not aware yet for conservation and maintenance the environment for support their livelihood. As a consequence, the people more often destructing the environment, for example illegal logging and land conversion. Beside that, developing community are often not consider the master plan and it need action for avoiding the people from disaster like landslide. There are a lot of factor that have to attention for reduction and friendly with landslide hazard in environmental friendly. V egetatif selection for prevention landslide become one of important key to success in prevention landslide hazard. The most important factor in landslide are the slope and the rainfall. Landslide could be anticipation with vegetatif selection. The vegetation must have root that could hold the stability of soil, that is deep root. The root have role in holding soil layer, therefore the vegetation with more multiple roots will more stronger in holding the soil, then the land stability increased. Other component in vegetation that have important role in landslide prevention is crown density. Higher crown density it .means the crown have more capacity to catch rainfall with interseption. In landslide hazard reduction, higher interseption could reduce volume of rainfall and it will reduce over land flow. In other side, high crown density also could increase soil mechanics weight, it could be cause of landslide. Finally, vegetation could be use for reduce landslide hazard, but it need strategy in vegetatif selection.